(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Mathematics is recognised as an essential subject in the Indonesian curriculum; however, many students still perceive it as frightening, particularly in topics involving multiplication and division of fractions. This study examined the effect of Joyful Learning on mathematics learning outcomes of Grade VI students at SDN 33 Pontianak Utara. The research employed a pre-experimental One Group Pretest–Posttest design with a sample of 28 purposively selected students who demonstrated low formative assessment scores on fraction operations. Data were collected through tests, documentation, and classroom observation, and analysed using descriptive statistics, normality testing, paired sample t-test, and effect size. The pretest showed an average score of 60.21, with only 21.4% of students meeting the KKTP. After the Joyful Learning intervention implemented through applause-based reinforcement, energizers, and game-based problem-solving the posttest mean increased to 76.64, with 67.9% of students achieving the KKTP. The paired sample t-test indicated a statistically significant improvement (|t| = 10.603; p < 0.001). To avoid misinterpretation of statistical results, the significance conclusion was based on the absolute comparison |tcount| > ttable (1.70329). Moreover, effect size analysis yielded a Cohen’s d value of 2.00, indicating a very large practical impact of the intervention. These findings suggest that Joyful Learning substantially enhances students’ comprehension of fraction multiplication and division, both statistically and practically. Nonetheless, given the limitations of the One Group Pretest–Posttest design, future research should adopt a quasi-experimental design with a control group to yield stronger causal inferences.